Digitalization of Islamic Preaching Communication as a New Civilization in the Field of Islamic Preaching - Hardi, Luthfi; Jaya, Canra Krisna (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digitalization of da'wah communication as a new civilization in spreading the message of Islam in the era of technology is a necessity. Digitalization provides a great opportunity to expand the reach of da'wah, allowing religious messages to be delivered quickly and effectively through various digital platforms such as social media, instant messaging applications, and websites. With a qualitative approach, with descriptive delivery from data sources, this study analyzes the use of technology in da'wah, as well as its impact on public perception. The results of the study show that the digitalization of da'wah communication not only increases the interactivity between da'wah and audience, but also forms a new pattern in delivering religious information that is more inclusive and adaptive. This paper concludes that the digitalization of da'wah is part of a new civilization that enriches da'wah methods, although it still requires supervision of the potential for misuse of information and data hacking